Encoding and updating spatial information presented in narratives. Issue 4 (April 2013) - Avraamides, Marios N.; Galati, Alexia; Pazzaglia, Francesca; Meneghetti, Chiara; Denis, Michel
Four experiments investigated whether directional spatial relations encoded by reading narratives are updated following described protagonist rotations. Participants memorized locations of objects described in short stories that placed them, as the protagonist, in remote settings. After reading a description that the protagonist rotated to the left or the right of the initial orientation, participants made judgements about object relations in the described environment (Experiment 1). Before making these judgements, participants were instructed to physically rotate to match (Experiment 2) or mismatch (Experiment 4) the protagonist's described rotation and in Experiments 3 and 4 to also visualize the changed relations following rotation. Participants' performance suggested that they relied on the initial representation they constructed during encoding rather than on the updated protagonist-to-object relations. Participants' physical movement to match the described rotation and additional visualization instructions did not facilitate updating through a sensorimotor process. In these respects, updating spatial relations in situation models constructed from narratives differs from updating in perceptually experienced environments.